The feed-in tariff (FIT) policy to improve renewable energy utilization: An analysis of FIT implementation in ASEAN countries from renewable energy growth, decarbonization, and investment perspective - Mujammil Asdhiyoga Rahmanta; Ari Permana; Wilson Susanto; Endiarjati Dewandaru Sadono; Irine Handika Ikasari; Muhammad Akhsin Muflikhun (International Journal of Renewable Energy Development, 2023)
The FIT policy are widely adopted in the world to promote the utilization of renewable energy technology (RET). Tariff rates, tariff regression mechanisms, contract term, and quota constraints are all components of the FIT policy. This policy has also been adopted by Association of Southeast Asian Nations or ASEAN countries to optimize their renewable energy (RE) potential. This paper examines the utilization of RET in power generation under the FIT policy from the perspective of the growth of renewable energy, environment, and investment which applied in five major ASEAN countries in term of the biggest generation capacity, such as: Indonesia Vietnam, Malaysia, Thailand, and the Philippines. This study shows that the FIT has been successful in accelerating renewable energy growth compared to pre-FIT, where annual RE capacity growth was 7.52% in Thailand (2007-2021), 16.38% in Vietnam (2011-2021), 4.56% in Indonesia (2012-2021) 2021), 9.11% in Malaysia (2012-2021), and 5.21% in the Philippines (2012-2021). FIT also managed to keep CO2/kWh emissions production stable in Vietnam, Malaysia, and Thailand while increasing RE production in their power systems. Otherwise, due to the low utilization of RET in Indonesia and the Philippines, CO2 emissions in them has increased significantly, 6.67% per year at Indonesia, and 15.25% per year at the Philippines after the introduction of the FIT. Generally, FIT has succeeded in increasing the value of international funding investments in RE sector in Indonesia, Vietnam, Malaysia, Thailand, and the Philippines